A level playing 'field'? A Bourdieusian analysis of the career aspirations of further education students on sports courses. Issue 8 (16th November 2016) - Connolly, Daniel J.; Allen-Collinson, Jacquelyn; Evans, Adam B.
Abstract : There is currently a distinct dearth of research into how sports students' career aspirations are formed during their post-compulsory education. This article, based on an ethnographic study of sport students in tertiary education, draws on data collected from two first-year cohorts ( n = 34) on two different courses at a further education college in England. The study draws on ethnographic observations, and semi-structured group interviews, to examine in-depth the contrasting occupational perspectives emergent within these two groups of mainly working-class students, and how specific cultural practices affect students' career aspirations. Utilising a Bourdieusian framework, the paper analyses the internalised, often latent cultural practices that impact upon these students' diverse career aspirations. The hitherto under-researched dimension of inter-habitus interaction and also the application of doxa are outlined. The article reveals how the two student cohorts are situated within a complex field of relations, where struggles for legitimisation, academic accomplishment and numerous forms of lucrative capital become habituated. The study offers salient Bourdieusian-inspired insights into the career aspirations of these predominantly working-class students and the ways in which certain educational practices contribute to the production and reproduction of class inequalities.